2009
DOI: 10.1007/s10535-009-0029-8
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of inbreeding depression between outcrossing and selfing <sub>Serapias</sub> species

Abstract: We quantified inbreeding depression for fruit production, embryo vitality and seed germination in three deceptive orchids, Serapias vomeracea, S. cordigera and S. parviflora, which do not provide any reward to their pollinators, and are predicted to experience high outcrossing. Of the three species examined only S. parviflora was autonomously selfing. Both S. vomeracea and S. cordigera showed highly significant differences in fitness between selfed and outcrossed progenies, resulting in high levels of inbreedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
2
18
1
1
Order By: Relevance
“…In agreement with previous studies, which reported that seed germination produced from cross-pollination was higher than self-pollination (Bellusci et al 2009). Self-pollination may have caused inbreeding depression (Charlesworth andCharlesworth 1987, Irawati 2013), resulting in decrease rate of seed viability, seed germination and seed survival (Husband and Schemske 1995).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies, which reported that seed germination produced from cross-pollination was higher than self-pollination (Bellusci et al 2009). Self-pollination may have caused inbreeding depression (Charlesworth andCharlesworth 1987, Irawati 2013), resulting in decrease rate of seed viability, seed germination and seed survival (Husband and Schemske 1995).…”
Section: Resultssupporting
confidence: 93%
“…In addition, the germination achievement of orchid seed often depends on pollination aspects. Seeds derived from self-and cross pollination particularly affect seed viability and enhance seed germination (Bellusci et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Inbreeding depression plays a central role in mating system evolution. The consequences of it have also become an important issue in conservation biology, and it is currently considered to be one of the most important threats to the persistence of rare taxa (Hedrick and Kalinowski, 2000;Bellusci et al, 2009). However, inbreeding depression has not been studied in R. pseudoacacia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the apparent reduced levels of selfing at DN may explain why the seeds from this population often outperformed those from other provenances regardless of where they were grown. Due to genetic purge, inbreeding depression is supposed to have less impact in selfers than in obligated outcrossers (Crnokrak and Barret, 2002) but several studies have reported larger seed production and greater seed performance for plants reproduced by outcrossing rather than selfing (Bellusci et al, 2009;Sletvold et al, 2012). The reasons of why plants at this site may behave differently are difficult to grasp and we are left to speculate.…”
Section: Discussionmentioning
confidence: 96%